Epidemiological and Clinical Characteristics of Elderly Fall Patients Visit to the Emergency Department: A Comparison by Gender - Jun Kew Kim; Sun Pyo Kim; Sun Hyu Kim; Gyu Chong Cho; Min Joung Kim; Ji Sook Lee; Chul Han (Journal of Trauma and Injury)
Purpose This study was to analyze clinical and epidemiological characteristics of elderly patients who were admitted to the emergency department (ED) due to falls by separating male and female. Methods We retrospectively analyzed the fall patients aged 65 years or older from the data of the in-depth surveillance study of injured patients visit to the ED under the supervision of the Korea Centers for Disease Control and Prevention (KCDC) from 2011 to 2016 by separating male and female. Results A total of 361,588 elderly fall patients were analyzed and, among them, 14,429 (37.3%) were males and 24,208 (62.7%) were females. Male and female showed similar frequency of damage happening season. However, they showed falling accident mostly on winter. The time of injury occurrence is mostly from 12:00 to 18:00 with 4,949 (34.3%) male and 8,564 (35.4%) female. Most falls occurred in daily activities, accounting for 7,614 (52.8%) in males and 14,957 (61.8%) in females, respectively. Unintentional damage accounted for the most part and 7,395 (51.2%) of male and 15,343 (63.4%) of female were injured indoors. Head and neck were the most common site of injuring, with 8,392 (58.2%) in males and 7,851 (32.4%) in females. According to ED examination outcomes, most of the patients were discharged, while the majority of the hospitalized patients were admitted to the general patient room. Conclusions The elderly falls occurred mostly from 12:00 to 18:00, during winter and to elderly women. Also, they happened unintentionally indoors in everyday life, mostly. Proved clinical, epidemiological characteristics from this research will be used as useful indicator at validity research of development of prevent program of falling accident for elderly people.